PROMOTING LECTURER HAPPINESS: THE IMPACT OF HUMAN RESOURCE STRATEGIES AND ORGANIZATIONAL SUPPORT IN HIGHER EDUCATION - Purbo Jadmiko; Elfitra Azliyanti; Linda Wati; Suci Dzakiratul Jannah (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This study examines the impact of human resource practices, perceived organizational support, and Religiosity on employee happiness at work. Utilizing a quantitative research method, data were collected through surveys from 115 academic staff at Padang City (google form). The research instrument was tested using Confirmatory Factor Analysis (CFA) and multiple linear regression for hypothesis testing (STATA). The findings reveal that effective human resource practices and perceived organizational support significantly enhance employee happiness, whereas Religiosity does not show a substantial effect. The implications suggest that organizations should focus on supportive HR practices and fostering organizational support to improve employee well-being. This research contributes to the understanding of factors influencing workplace happiness and offers practical insights for HR management in higher education institutions.Keywords: happiness at work, religiosity, perceived organizational support, human resources practices,